PENGARUH DISIPLIN KERJA TERHADAP SEMANGAT KERJA PEGAWAI KANTOR KESYAHBANDAR DAN OTORITAS PELABUHAN KELAS II SAMARINDA - Laurentinus Langga (ADMINISTRASI PUBLIK, 2019)
This study aims to determine how much influence the work discipline has on employee morale in the Kesyahbandar office and class II port authority in Samarinda. The research method used is quantitative. The sample in this study amounted to 98 employees. Data collection techniques used were observation, interviews, and distributing questionnaires. The analytical method used is simple linear regression, validity, reliability, and coefficient of determination.The results of the study state that work discipline, and the morale of employees of the Kesyahbandar office and class II port authorities in Samarinda can be said to be very good. work discipline has a strong influence on employee morale which is equal to 75.9%. while the remaining 24.1% is influenced by other variables. From the hypothesis test by using the t test, the value of t arithmetic is 8,847 greater than t table of 1,661, so the proposed hypothesis is accepted.